CALCULATION OF PAYBACK PERIOD MINERAL WOOL WITH LONGITUDINAL FIBERS OF ITE PARISO (PAREXLANKO) - Vatin, Nikolay Ivanovich; Gorshkov, Alexander; Kazimirova, Alexandra; Gureev, Kirill; Nemova, Darya (Journal of Applied Engineering Science, 2014)
The article presents a calculation of an energy-saving payback system aimed at enhancing thermal protection of enclosing structures of a panel-assembled building in use by means of the ITE PARISO thermal insulation products. Examples are given of how to calculate the simple payback period of extra insulation of buildings’ exterior walls by ITE PARISO slabs and of how to calculate the payback period taking into account the growth of rates for thermal energy.